(untitled) (Cần Thơ, 1999)
This book is an alphabetical compendium of nautical terms taken from numerous dictionaries, glossaries and other sources of nautical terminology, including volumes on nautical customs and traditions, ghost ships, paranormal maritime events, sea serpents, and marine monsters.
Keywords: Water resources development,Trung tâm Học liệu ĐHCT,Water; Phát triển nguồn nước,Study and teaching